Design and Construction of Block and Tackle Pulley System Using Locally Available Resources. - Asaba, Patrick (Kabale University, 2024)
Physics students are finding it difficult to pass questions on applications in simple mechanics since they are taught in a way that they cannot see these machines in reality working. To improve their performance, at least one of the machines has to be designed to work as a teaching aid such as a pulley system such that students can use them to experiment as they learn how they work. This project, therefore, is about the design and construction of a Block and Tackle Pulley System using locally available materials. The overall implementation of this work involves knowledge of the physics of mechanics, particularly simple machines. As a case study, I used a fixed pulley and a moveable pulley in the construction of an improvised Block and Tackle system. I hypothesize that using a fixed pulley and a movable pulley increases mechanical advantage. Therefore, my improvised block and tackle system was constructed using a fixed pulley, a moveable pulley, a rope, a Hole cutter/hole saw, a Baw saw, a Plane, a Tape measure, a Pencil, a Grooving machine, a Jig saw, Hammer.